Ellagic Acid Bioavailability and Metabolism After Single Dose Consumption of Pure Ellagic Acid versus Pomegranate Juice (P06-031-19). (13th June 2019) - Long, Jianfeng; Yang, Jieping; Guo, Yuanqian; Henning, Susanne; Lee, Rupo; Rasmusen, Anna; Zhang, Lijun; Lu, Qinyi; Heber, David; Li, Zhaoping
Abstract: Objectives: In the GI tract, Pomegranates (Pom) ellagitannins undergo hydrolysis to ellagic acid (EA) and are further metabolized into urolithins by the gut microbiota. Both EA and UA have significant health benefits. EA is also available as dietary supplement. We aimed to compare the bioavailability of EA and its biotransformation to UA between pure EA and Pom juice (PomJ). Methods: 17 healthy male participants were randomly assigned to take a single dose of 8 oz of PomJ or 500 mg of EA, followed by 2-week washout, and crossover to the other intervention. We collected blood prior and 1 and 2 h after consumption of EA or PomJ and urine for 24hours. Plasma concentration of EA was measured using HPLC. Urinary EA metabolites (DMEAG and UAG) were determined by LC/MS and normalized to urine creatinine levels. Circulating MCP1, insulin and leptin were analyzed using the multiplex human cytokine panel (Millipore). Results: There was no difference in plasma EA concentration after administration of PomJ versus 500 mg EA. Urinary DMEAG, normalized to creatinine, was significantly higher after PomJ compared to EA intake (PomJ: 0.11 + 0.02; EA: 0.05 + 0.01 µg/mg; P < 0.05). Urinary UAG was present in 13 participants and 4 out of 17 subjects did not have the ability to convert EA to UA after consumption of either pure EA vs. PomJ. Blood glucose at 2 hrs decreased −5.53% ± 1.61% (p = 0.01) and insulin at 1 hr increased 95.74% ± 37.44% (p < 0.05) after PomJ consumption compared to baseline. Blood MCP1 decreased −15.51% ± 6.11% (p < 0.05) 2 hrs after PomJ, and leptin was significantly decreased (PomJ: −17.13% ± 4.64% (p < 0.00); EA: −18.80% ± 2.93% (p < 0.00)) 2 hrs after PomJ and EA consumption. Conclusions: 8 oz of PomJ provides an equivalent source of EA and microbial mediated biotransformation of EA to UA compared to 500 mg EA supplement. However, an increase in phase II metabolism of EA and acute effect on plasma MCP1 was only observed following PomJ consumption. Funding Sources: Center for Human Nutrition, David Geffen School of Medicine at UCLA, Los Angeles.